2021
DOI: 10.3390/diagnostics11061051
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CAG Repeats within the Non-Pathological Range in the HTT Gene on Cognitive Functions in Patients with Subjective Cognitive Decline and Mild Cognitive Impairment

Abstract: The Huntingtin gene (HTT) is within a class of genes containing a key region of CAG repeats. When expanded beyond 39 repeats, Huntington disease (HD) develops. Individuals with less than 35 repeats are not associated with HD. Increasing evidence has suggested that CAG repeats play a role in modulating brain development and brain function. However, very few studies have investigated the effect of CAG repeats in the non-pathological range on cognitive performances in non-demented individuals. In this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We already showed that CAG repeat lengths in HTT may differently influence neuropsychological performances according to cognitive status of subjects ( 14 ). In more detail, we showed that a higher number of GAC repeats in the non-pathological range was associated with higher scores in tasks assessing executive function, memory, visual–spatial ability and language in SCD patients but to lower scores in the same cognitive domain in MCIs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We already showed that CAG repeat lengths in HTT may differently influence neuropsychological performances according to cognitive status of subjects ( 14 ). In more detail, we showed that a higher number of GAC repeats in the non-pathological range was associated with higher scores in tasks assessing executive function, memory, visual–spatial ability and language in SCD patients but to lower scores in the same cognitive domain in MCIs.…”
Section: Resultsmentioning
confidence: 99%
“…The biological substrate of this effect might lie in the interaction of HTT protein with a number of proteins with a role in microtubule-based axon trafficking ( 33 , 34 ). In particular, wild-type Hintingtin protein specifically enhances the vesicular transport of Brain Derived Natriuretic Factor (BDNF) ( 35 ), a neurotrophic factor involved in synaptic connections ( 36 ), neural growth ( 37 ), synaptic plasticity ( 38 ), and essential for long-term potentiation underlying hippocampus-related memory ( 14 , 39 ). PolyQ tracts in Huntingtin protein stabilize interactions ( 40 ), according to a non-linear relation with the best function reached at an intermediate number of CAG repeats and then showing a progressive decrease ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that increasing repeat length below the disease threshold in HTT confers advantageous changes in brain structure (cerebral cortex thickness [38] and gray matter within the pallidum [39]) and is associated with greater general intelligence and visual‐perceptual skills [38]. Nevertheless, in a previous study by our group, we showed that a higher number of CAG repeats in the HTT gene (below the pathological threshold) positively influenced memory, visual‐spatial ability, executive function and language in SCD patients, but negatively affected cognitive function in MCI [40]. Therefore, we speculated that higher number of CAG repeats in the HTT gene might enhance cognitive function in cognitively healthy subjects and in patients with subjective impairment, but, as cognitive impairment advances, this advantage fails and longer repeat length begins to play a detrimental effect.…”
Section: Discussionmentioning
confidence: 99%